SPATIAL PATTERNS OF ISLAMIC RELIGIOUS ACTIVITIES IN KRAPYAK DISTRICT, YOGYAKARTA - Rizky Adi Sudrajad; Bambang Hari Wibisono (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2021)
Krapyak District is one of the significant areas in Yogyakarta, crossed by thePhilosophical Axis stretching from Tugu in the North to Panggung Krapyak inthe South end. The Javanese philosophy of Sangkan Paraning Dumadi lieswithin the axis. In 2017, based on the Special Region of YogyakartaGovernor's Decree Number 108, this axis was designated as the part of thecultural heritage. As stated in the decree, the areas around the philosophicalaxis must represent the meaning of Sangkan Paraning Dumadi, both in termsof activities and spaces. Furthermore, the presence of Islamic boardingschools, also known as pesantren, helps to transform Krapyak District into asolid Islamic community. This study aims to identify the relation betweenactivity patterns and the built environment in Krapyak District. The harmonybetween activity patterns, the built environment, and the meaning of acomplex philosophical axis of Krapyak District is fascinating to investigate,especially in light of the district's environmental issues. This study used adeductive approach with a descriptive-qualitative method based on thebehavioral space system model of place-centered mapping. It is concludedthat there are three layers of activity and space, namely the religious layer,the socio-cultural layer, and the philosophical axis layer, that interact oneanother with some specific spatial patterns.